2020
DOI: 10.1007/s00595-020-02063-x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of surgery for clinical stage IA lung cancer in Japan: analysis of the national clinical database

Abstract: Purpose As the number of cases of early lung cancer in Japan grows, an analysis of the present status of surgical treatments for clinical stage IA lung cancer using a nationwide database with web-based data entry is warranted. Methods The operative and perioperative data from 47,921 patients who underwent surgery for clinical stage IA lung cancer in 2014 and 2015 were obtained from the National Clinical Database (NCD) of Japan. Clinicopathological characteristics, surgical procedure, mortality, and morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The NCD is a nationwide web-based surgical patient registration system, which enables the collection of data on all surgical procedures performed in Japan, in addition to perioperative factors. More than 14,340,000 procedures, accounting for more than 90% of all surgeries performed in Japan during this period, have been registered by approximately 5,000 hospitals [ 6 , 7 ]. The NCD constructed software for an Internet-based data collection system and data managers in participating hospitals were responsible for forwarding their data to the NCD office [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…The NCD is a nationwide web-based surgical patient registration system, which enables the collection of data on all surgical procedures performed in Japan, in addition to perioperative factors. More than 14,340,000 procedures, accounting for more than 90% of all surgeries performed in Japan during this period, have been registered by approximately 5,000 hospitals [ 6 , 7 ]. The NCD constructed software for an Internet-based data collection system and data managers in participating hospitals were responsible for forwarding their data to the NCD office [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the definition of surgical approaches, although each definition for VATS and mini-thoracotomy varied among reports, we basically adapted the definition of the national clinical database (NCD) registry in Japan. 21) According to this registry, all approaches with skin incision <8 cm regardless of the presence or absence of a rib spreader are registered as VATS. Moreover, the VATS cases in the NCD registry were divided into complete VATS (surgical manipulation under only monitor vision) and VATS+mini-thoracotomy (surgical manipulation under combined use of monitor and direct vision).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, PBT may be advantageous if operative mortality increases due to an underlying disease, even for young patients, whereas lobectomy may be advantageous for patients with underlying diseases, even for older patients. In addition, several studies have reported operative mortality can be reduced and that there is no difference in disease control rates when minimally invasive surgery like VATS and RATS are performed rather than an open thoracotomy [ 38 , 56 , 57 ]. When determining a treatment modality, it should be considered which surgical technique will be used.…”
Section: Discussionmentioning
confidence: 99%